Long-Term Effects of an Intensive Lifestyle Intervention on Electrocardiographic Criteria for Left Ventricular Hypertrophy: The Look AHEAD Trial - Brinkley, Tina E (Am J Hypertens, 2018)
BACKGROUND: Left ventricular hypertrophy assessed by electrocardiography (ECG-LVH) is a marker of subclinical cardiac damage and a strong predictor of cardiovascular disease (CVD) events. The prevalence of ECG-LVH is increased in obesity and type 2 diabetes; however, there are no data on the long-term effects of weight loss on ECG-LVH. The purpose of this study was to determine whether an intensive lifestyle intervention (ILI) reduces ECG-LVH in overweight and obese adults with type 2 diabetes. METHODS: Data from 4,790 Look AHEAD participants (mean age: 58.8 ± 6.8 years, 63.2% White) who were randomized to a 10-year ILI (n = 2,406) or diabetes support and education (DSE, n = 2,384) were included. ECG-LVH defined by Cornell voltage criteria was assessed every 2 years. Longitudinal logistic regression analysis with generalized estimation equations and linear mixed models were used to compare the prevalence of ECG-LVH and changes in absolute Cornell voltage over time between intervention groups, with tests of interactions by sex, race/ethnicity, and baseline CVD status. RESULTS: The prevalence of ECG-LVH at baseline was 5.2% in the DSE group and 5.0% in the ILI group (P = 0.74). Over a median 9.5 years of follow-up, prevalent ECG-LVH increased similarly in both groups (odds ratio: 1.02, 95% confidence interval: 0.83–1.25; group × time interaction, P = 0.49). Increases in Cornell voltage during follow-up were also similar between intervention groups (group × time interaction, P = 0.57). Intervention effects were generally similar between subgroups of interest. CONCLUSIONS: The Look AHEAD long-term lifestyle intervention does not significantly lower ECG-LVH in overweight and obese adults with type 2 diabetes. CLINICAL TRIALS REGISTRATION: Trial Number NCT00017953 (ClinicalTrials.gov)